Dismissal for operational requerments [sic]:comparison between South Africa and English Labor Law - Nkgapele, Mmakgwana Freddy (University of Limpopo, 2010)
Refer to document
Dismissal for operational requirements [sic]:comparison between South Africa and English Labor Law
Thesis (LLM) --University of Limpopo, 2010
Keywords: Employee dismisal; Dismissal for operational requirements; Employees - Dismissal of - Law and Legislation -- South Africa